What do we know about the future of crop pests and diseases in relation to food systems? - Petsakos, Athanasios; Montes, Carlo; Pequeno, Diego; Schiek, Benjamin; Sonder, Kai (International Food Policy Research Institute, 2025)
Crop pests and diseases (P&D) can cause substantial yield losses and pose a threat to global food security. Losses at a regional level can even exceed 40 percent for crops like maize and rice.